The Effect of Small Side Games Training with Different Field Sizes on Improving Dribbling Skills in 15-Year-Old Football Players - Syahrul Ghazi Parasutama; Dede Rohmat Nurjaya; Yudi Nurcahya (Universitas Negeri Semarang, 2025)
This study aims to analyze the effect of small-sided games training with different field sizes on the dribbling skills of 15-year-old soccer athletes. The study used a quantitative approach with a pretest–posttest control group experimental design. The study subjects were 20 15-year-old soccer athletes who were randomly divided into an experimental group and a control group with an equal number. The experimental group was given small-sided games training with varying field sizes, while the control group underwent small-sided games training without varying field sizes. Dribbling skills were measured using a zig-zag dribbling test at the pretest and posttest stages. Data were analyzed using descriptive statistics as well as prerequisite tests and independent t-tests. The results showed that small-sided games training with different field sizes provided more effective dribbling skill improvements than training without varying field sizes. Variations in field sizes created more diverse technical and situational demands, thus encouraging more optimal adaptation of ball control, agility, and player decision-making. These findings confirm that field size adjustment is an important factor in the application of small-sided games in the development of adolescent soccer athletes.